THE EFFECTIVENESS OF SPATIAL ORDER IN WRITING A DESCRIPTIVE TEXT - Yuninan, Endru Dwi; Isnani, Zakiya (E-Link Journal, 2020)
Students sometimes face some difficulties to make a writing. They have difficulties to change the sentence into a good paragraph and how to combine it as a good text structure. This research used a spatial order technique in writing a descriptive text. Spatial Order is a technique of writing based on the space in the order. The purpose of the research is to know the effectiveness of the spatial order technique in writing a descriptive text, and how is the student's response towards it. The research is conducted in MA Sains Roudlotul Qur'an. The research used pre-experimental research with one group pre-test and post-test design. The sample is X MIPA 2 class with using purposive sampling technique to choose the sample. The data from the test is analyzed using t-test checking to find the significance of the data. On the other hand, the data from the questionnaire is analyzed with finding the percentage of the data. The result of the research shows that the number of t-tests which is to find the effectiveness of the technique is 6,65. It is higher than t-table score at significance 0,1 that is (t-test=6,65 > t-table =1,69). By means, Ha that it is Effective to use spatial order in writing a descriptive text is accepted. On the other hand, the respond of the students showed that 78% of the students give positive feedback in using this technique. By means, the students give a positive response to this technique.Â